They Who do not Grieve - Figiel, Sia (Chatto & Windus, 2000)
Sia Figiel's powerful, poetic skills weave together the voices of three generations of women from two Samoan families. Their dream worlds and realities intermingle, just as the histories of each generation run through the next. At the center of the novel is the Samoan woman's tattoo, the "malu," believed to be brought from Fiji by Siamese twins. The ghosts of the twins watch over the women whose lives are stained by an unfinished tattoo. The shame and grief of not completing the tattoo ceremony go hand in hand with the shame and grief of illicit love and broken promises.
Keywords: Juvenile Fiction